Introduction to recetivism - Dura, Adam A. (Folia Philosophica, 2004)
The following article is an attempt at introducing a new philosophical system called recentivism. The author pays attention to the fact that it appears - in its present form - in the view of philosophical postmodernism. The present state of contemporary philosophy - in the face of failures of philosophical projects of the 20,h century - is an introduction to new universal syntheses. Józef Bańka, almost meeting the times halfway, puts forward recentivism, a maximalistic system that can be included in the tempo-centric trend of philosophy. The original method of philosophizing a recentiori, identification of being and presence [ens et recens converturtur], appreciation of the current moment of truth in epistemology, new anthropological project of homo euthyphronicus, concept of ethics of simple-mindedness, historiosophical views, and lately a postulate of euro-recentivism - are all factors allowing inspirations in the interpretation of reality. Even more - recentivism has been researched in the Institute of Philosophy of the Silesian University [and not only there]. This new philosophical system in a shape of a wide research material awaits analysis and wide confrontation with other philosophical stances.